A rare subtype of meningioma: Case series of anaplastic meningioma and review of the literature. Issue 23 (June 2018) - Cao, Hongyi; Jiang, Biying; Zhao, Yang; Fan, Chuifeng
Abstract: Rationale: Anaplastic meningioma, a rare subtype of meningioma, has malignant morphological characteristics and a World Health Organization (WHO) grade of III. Patient concerns: In this report, we present findings from 6 cases of anaplastic meningioma. Diagnoses: Pathological examination of the tumors, including hematoxylin and eosin staining and immunohistochemical staining, was performed. Of the six cases of anaplastic meningioma, two were recurrent tumors from original seminoma with a WHO grade of I. Histologically, three cases had carcinoma-like morphology, one case had sarcoma-like morphology, and two had two kinds of tissue structures: carcinoma-like tumor cell nests and areas with spindle tumor cells. Necrosis was detected in most cases (5/6). Ki67 index was high and varied from 20% to 70%. Interventions: All the patients received surgery. 3 patients received adjuvant radiotherapy. 1 patient received chemotherapy. Outcomes: 4 patients had no recurrence at follow-up of 19, 30, 46 and 54 months after the last surgery. 1 patient had recurrence 3 months after the last surgery. 1 patient died 12 days after the last surgery. Lessons: This malignant subtype can be secondary to a WHO grade I meningioma after a long quiescent period. Necrosis was common in the tumor tissues, and Ki67 index was usually high. For patients with a history of meningioma, including benign cases, regular physical examination is important for early detection of tumor recurrence and malignant transformation.